Analisis Minat Investor Milenial Berinvestasi Pada Securities Crowfunding Syariah (Studi Kasus Galery investasi di kota Medan) - Aninda Mahfadillah; Andri Soemitra; Muhammad Ikhsan Harahap (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This research was conducted with the aim of knowing the effect of investment knowledge, motivation and risk variables on the millennial generation's interest in investing in Securities Crowdfunding Sharia Gallery investment. Research using a quantitative approach. The technique of data collection was carried out using purposive sampling, and the sample used was 88 respondents. Data collection was carried out using a questionnaire with a Likert scale. The method used in this research analysis is a linear regression analysis method. The results of the Knowledge t test research (X1) show that partially knowledge influences the millennial generation's interest in investing in Sharia Securities Crowdfunding. Motivation (X2) that partially motivation influences the millennial generation's interest in investing in Sharia Securities Crowdfunding. Risk (X3) that partially does not affect the millennial generation's interest in investing in Sharia Securities Crowdfunding. The results of the f test show that simultaneously knowledge, motivation and risk affect the millennial generation's interest in investing in Sharia Securities Crowdfunding.